All is leaf : essays and transformations - Price, John, 1966- (Bur oak book., 2022)
"All is Leaf is John Price's fifth book of creative nonfiction, and picks up many of the central themes that have drawn readers to his earlier work-parenting, nature, childhood, community, spirituality and the writing life. It also frequently uses the humorous style for which he's become known. But these themes take on new shape and substance in the more experimental approaches found in All is Leaf. The essays are written from Price's perspective as a parent, husband, friend, teacher, writer, environmentalist and citizen. The title was inspired by the philosophies of both Goethe and Thoreau, who felt that change and transformation-personal, societal, environmental-were best embodied by plant leaves. The form of All is Leaf reflects this theme: sixteen essays that employ multiple forms and voices, all rooted in personal experience, but intended to reflect and respond to the rapidly changing nature of our times. It is a collection ideally positioned for use in the classroom, offering students (and teachers) examples of, and reflection on, a wide range of essayistic possibilities. Many of the pieces were written with younger, college-age audiences in mind. In essays such as "My Rock-n-Roll Road Song," "My Wild Animal Attack Story," "My Essay on the Essay," "My Rankin/Bass Christmas Special," "My Epic Norse Saga to Live By," "My Science Fiction Horror Story," and so on, ordinary life, it seems, is far from ordinary. The people and places and vocations and democracy we sometimes take for granted-and the too-often unexpressed, inconsistent, messy love we feel for them-have now taken on new significance in our era of uncertainty. Or should. All is Leaf, through an unconventional mix of voices and forms, seeks to elevate those daily experiences to a more deserving level of moral, even mythic significance, whether in Price's life or in the lives of readers"--